(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Trauma is a serious health problem especially when an individual is poor. They cannot reach hospital timeously, and also could not afford to get a quality of care in hospital. Transkei is the poorest region in South Africa with poor infrastructure like transport and health care. Objective: To study the incidence of blunt force trauma deaths in the Transkei sub-region of South Africa. Method: An autopsy record review study at Forensic Pathology Laboratory at Mthatha over a period of 23-years (1993-2015). Results: There were 26 855 autopsies were conducted over the period of 23 years. Of this, 2960 (11 %) deaths are related with blunt force trauma. Majority were males 2477 (9.2%). The male to female ratio is 6:1. About one-fourth 720 (30.21%) are between 21 and 30 years of age group. The average blunt force trauma fatalities is 20.2 per 100 000 per year. The highest rate of deaths, 25 per 100 000 has recorded in the year Conclusion: There has been an increasing trend of deaths as a result of blunt force trauma in the Transkei sub-region of South Africa. Poverty is probably a major underlying factor in these deaths.